Analysis of the Effect of Rainwater Infiltration on Slope Stability Using the Limit Equilibrium Method at the Outpit Disposal, Serongga Site, PT Baramega Citra Mulia Persada - Hulwani, Zati; Muhammad Hanif Khuzaifi; Nurul Aflah; Abrar Muslim; Yoessi Oktarini; Pocut Nurul Alam (Jurnal Serambi Engineering, 2026)
Slope stability in mining areas is a critical aspect that must be carefully considered, particularly in regions with high rainfall intensity. Heavy rainfall can increase the risk of slope failure, disrupt mining operations, and reduce planned production targets. This study investigates the effect of rainfall infiltration on slope stability at PT Baramega Citra Mulia Persada, Kotabaru, South Kalimantan, Indonesia. The Limit Equilibrium Method (LEM) using the Janbu method was applied to evaluate the Factor of Safety (FoS) under different moisture conditions and to assess the influence of rainfall infiltration on slope performance in the outpit disposal area. FoS calculations were conducted on four slope cross-sections, namely AA’, BB’, CC’, and DD’, based on geotechnical and rainfall data. The results indicate that each slope exhibits variations in FoS under different moisture conditions. Slope AA’ shows FoS values of 1.48 (saturated), 1.976 (partially saturated), and 2.007 (dry). Slope BB’ has FoS values of 1.311, 1.650, and 1.711, while slope CC’ exhibits FoS values of 1.516, 2.187, and 2.279. Slope DD’ represents the most critical condition, with the lowest FoS values of 1.106 (saturated), 1.374 (partially saturated), and 1.470 (dry). To improve stability, a geometric modification was applied to slope DD’ by adding an additional bench with a height of 4.3 m, which increased the FoS to 1.514 and satisfied the mine slope stability criteria.